Unusual achalasic sigmoid esophagus - Pandit, Narendra; Shrestha, Vijay; Awale, Laligen; Jaiswal, Lokesh Shekher (Journal of Society of Surgeons of Nepal, 2019)
Achalasia cardia is a rare primary esophageal motility disorder with an incidence of about 1 in 100,000 individuals. If left untreated or inappropriately treated, the disease may progress to end-stage achalasia characterized by megaesophagus or sigmoid esophagus. The presentation as severe malnutrition, anemia, hypoalbuminemia, and asymptomatic tracheal compression has not been described in the setting of the sigmoid esophagus, in absence of underlying malignancy. Here we report an interesting case of a young male, who presented with the above features and managed excellently by open Heller’s myotomy under epidural anesthesia due to the poor performance status.